The effect of an anatomical structure of a stem on pea lodging - V. L. Gaze; I. A. Lobunskaya; N. V. Yanovskaya; E. Yu. Cherpakova; A. R. Ashiev (Зерновое хозяйство России)
Currently, in our country there is growing interest in the cultivation of high-tech pea varieties, which are characterized by uniform maturity, high productivity, and lodging resistance. Thus, breeding for lodging resistance is one of the most important criteria in pea breeding programs. The purpose of the current study was to search for anatomical indicators that could serve as a criterion when selecting pea samples for lodging resistance. The field trials were carried out in the fields of the laboratory for legumes breeding and seed production, the laboratory study was conducted in the laboratory for cell breeding of the FSBSI “ARC “Donskoy” in 2022–2023. The estimation of lodging resistance was carried out on 22 pea samples of the regional and foreign breeding. The studied samples differed in plant height, morpho-anatomical features of a stem structure, and lodging resistance. Based on the results of estimating an anatomical structure of a pea stem, there were identified such samples with a complex of traits (number of bundles, ratio of a number of bundles to stem tissues) as ‘Lu-153-06’, ‘G-1234’, ‘G-1193’, ‘G-1288’, ‘AKM’, ‘G-1313’, ‘Flagman 10’, ‘G-1313’. The analysis of correlations between anatomical indicators and field resistance to lodging has shown a high positive correlation with a stem height (r = 0.78±0.14), a mean negative correlation with a plant height (r = -0.66±0.17), and a mean positive correlation with a number of vascular bundles (r = 0.69±0.16). The experimental results allow concluding that the estimation of lodging resistance based on an anatomical structure of a pea stem is effective and can serve as a tester for lodging resistance.